STRUKTUR KOMUNITAS PLANKTON PERMUKAAN PADA DANAU LABUAN CERMIN KEC. BIDUK-BIDUK, KAB. BERAU - Arum, Elis Seftia; Hariani, Nova; Hendra, Medi (Universitas Tanjungpura, 2018)
This study aims to determine (physico-chemical) parameters of water and also community structure of plankton surface in natural tourism Labuan Cermin Biduk-Biduk, Berau, Kalimantan Timur. This study used Purposive Sampling method. Data obtained shows in plankton abundance, diversity index, evenness index and dominance index. The result of study showed that range of temperature between 24,04 oC -26,88 oC, range of salinity between 0.25-0.87o/oowhich classified in freshwater-brackish water, range of power flow between 1.121-2.930 m/s which classified in moderate level, the average pH between 6,76-7,48 which classified in neutral level, range of TDS betweenÂ 514-788 mg/L which classified in normal level, respectively. Plankton sample showed 27 classes including of 22 classes of phytoplankton with 57 genera and 5 classes of zooplankton with 10 genera. The highest total plankton abundances ofÂ 35917 ind/L is in Station A and the lowest total plankton abundances of 8330 ind/L is in Station F. Keywords: Plankton, Labuan Cermin, Â Diversity.